RE: Biomechanical comparative analysis of temporomandibular joint, glenoid fossa and head of the condyle of conventional models prothesis with new PEEK design - Eric J. Granquist; Louis G. Mercuri; Gary Warburton (Elsevier, 2023)
This is a Letter to the Editor that describes some of the biomechanical concerns with the statements made in This is a LTE that raises some biomechanical statements made in Genovesi W, Comenale IC, Genovesi Filho W, Veloso Fernandes M. Biomechanical comparative analysis of temporomandibular joint, glenoid fossa and head of the condyle of conventional models prothesis with new PEEK design. J Oral Biol Craniofac Res. 2022 Sep-Oct; 12(5):529-541.